2022
DOI: 10.1039/d2sc02606f
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic catalytic aerobic oxidation of C–sp(3)–H bonds under mild conditions using galactose oxidase model compound CuIIL

Abstract: Developing highly efficient catalytic protocols for C-sp(3)-H bond aerobic oxidation under mild conditions is a long-desired goal of chemists. Inspired by nature, a biomimetic approach for the aerobic oxidation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…This means that the odd electron can be distributed on the whole skeleton. 62 The DFT simulation in Fig. 3(d) and (e) also revealed that the electron spin was delocalized within the two entire benzene rings and the conjugated N atom, corresponding to the π-electron localized orbital locator (LOL) of the MBH 2 2+ ˙ radical.…”
Section: Resultsmentioning
confidence: 91%
“…This means that the odd electron can be distributed on the whole skeleton. 62 The DFT simulation in Fig. 3(d) and (e) also revealed that the electron spin was delocalized within the two entire benzene rings and the conjugated N atom, corresponding to the π-electron localized orbital locator (LOL) of the MBH 2 2+ ˙ radical.…”
Section: Resultsmentioning
confidence: 91%
“…20 Our group has reported a ppm loading biomimetic catalyst, named Cu(HPTB), for boosting up the generation of N-oxyl radical to selectively afford MEK from n-butane, which showed a remarkable ∼30% conversion and 70% selectivity at 75 °C. 21 Although selective oxidations of hydrocarbons by NHPI have been extensively studied in the past decades, 22−25 the corresponding kinetics have received limited attention with quite a few reports, 26−29 for example, Zhang's group recently reported the kinetics of the NHPI-catalyzed aerobic oxidation of cyclohexylbenzene. 30 Therefore, encouraged by our promising findings in the high-value-added biomimetic utilization of nbutane feedstocks, we carefully conducted a kinetic study of oxidation from n-butane to MEK, which might help to prepare the way for further practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the oxidation of the α-C−sp(3)−H bond of lactate to pyruvate is extremely challenging for conventional chemical catalysts at mild conditions due to the high bond energy of the C−H bond. 7 Traditionally, oxidative dehydrogenation of lactate to pyruvate is unavoidable under high temperatures (typically over 200 °C) or pressure (e.g., over 1 MPa), greatly hindering the exploitation of nanozymes with lactate management ability. 8 LOX, a member of flavoenzyme, can specifically catalyze the oxidation of lactate to pyruvate.…”
Section: Introductionmentioning
confidence: 99%
“…Rational design of nanozymes with satisfactory lactate oxidase (LOX)-mimicking activities can encourage lactate-responsive tumor therapeutic strategies. However, the oxidation of the α-C–sp(3)–H bond of lactate to pyruvate is extremely challenging for conventional chemical catalysts at mild conditions due to the high bond energy of the C–H bond . Traditionally, oxidative dehydrogenation of lactate to pyruvate is unavoidable under high temperatures (typically over 200 °C) or pressure (e.g., over 1 MPa), greatly hindering the exploitation of nanozymes with lactate management ability .…”
Section: Introductionmentioning
confidence: 99%